The Aristocrats Power on Local Politic in The Regency of Bone 2013-2018 - Nursaleh Hartaman; Titin Purwaningsih; Achmad Nurmandi (Journal of Governance, 2020)
This research purpose is to examine the aristocrat's power in the perspective of habitus, capital, and arena. This type of research is qualitative. The results of the research show from the habitus perspective, the leadership of the descent line has gained legitimacy by the people with the “lontara” principle that is still held firmly by leaders from the aristocracy until now and Aristocrats has been prepared to become a leader from next generation. From Arena perspective, it can be seen that patronage of bureaucracy and parties has a great influence on the continuity of aristocratic power and the political system produces political opportunities that are influenced by the popularity and capacity, Finally, Capital owned by the aristocrats that are social, symbolic, economic and cultural, of the four capital the most powerful is capital symbolic because the title of aristocrat roommates then capitalized as a political tool to reap the votes in political contestation.